2017
DOI: 10.1038/srep40636
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous patterns of DNA methylation-based field effects in histologically normal prostate tissue from cancer patients

Abstract: Prostate cancer (PC) diagnosis is based on histological evaluation of prostate needle biopsies, which have high false negative rates. Here, we investigated if cancer-associated epigenetic field effects in histologically normal prostate tissue may be used to increase sensitivity for PC. We focused on nine genes (AOX1, CCDC181 (C1orf114), GABRE, GAS6, HAPLN3, KLF8, MOB3B, SLC18A2, and GSTP1) known to be hypermethylated in PC. Using quantitative methylation-specific PCR, we analysed 66 malignant and 134 non-malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 53 publications
1
25
1
Order By: Relevance
“…HOXB4, as a hematopoietic transcription factor, downregulates the expression of Prdm16, which is a proto‐oncogene necessary for self‐renewal and maintenance of murine hematopoietic stem cells . The other eight frequently methylated candidates (CCDC181, DPP4, BEND4, CTNND2, ELMO1, SFMBT2, C1QL3, MIR129–2) confirmed in our study have also shown hypermethylation in other malignancies (Table ) . Among them, SFMBT2 and MIR129–2 have been shown to act as tumor suppressors.…”
Section: Discussionsupporting
confidence: 78%
“…HOXB4, as a hematopoietic transcription factor, downregulates the expression of Prdm16, which is a proto‐oncogene necessary for self‐renewal and maintenance of murine hematopoietic stem cells . The other eight frequently methylated candidates (CCDC181, DPP4, BEND4, CTNND2, ELMO1, SFMBT2, C1QL3, MIR129–2) confirmed in our study have also shown hypermethylation in other malignancies (Table ) . Among them, SFMBT2 and MIR129–2 have been shown to act as tumor suppressors.…”
Section: Discussionsupporting
confidence: 78%
“…The AUCs of ST6GALNAC3 (0.917–0.995) were generally higher than those of ZNF660 (0.846–0.903) and were similar to those of other published diagnostic candidate methylation markers (Goering et al ., ; Haldrup et al ., , ; Kristensen et al ., ), suggesting that ST6GALNAC3 has promising diagnostic biomarker potential for PC tissue. To further assess this, it would be interesting to evaluate ST6GALNAC3 and ZNF660 promoter methylation also in cancer‐negative diagnostic biopsies, as promoter hypermethylation field effects in cancer‐negative diagnostic biopsies have previously been shown to predict the result of repeat biopsy (Moller et al ., ; Partin et al ., ; Stewart et al ., ; Trock et al ., ; Troyer et al ., ; Van Neste et al ., ). Results of such analyses should, for example, be compared to the commercially available urine‐based PCA3 assay (Progensa) and the tissue‐based methylation test ConfirmMDx (MDxHealth), both designed to determine whether a repeat biopsy is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Sample set 1 consisted of 20 PC (from RPs) and 21 NM (12 AN from RPs and 9 histologically normal from cystoprostatectomies) macrodissected fresh‐frozen samples (for clinicopathological data, see Table ), as described previously (Haldrup et al ., ; Moller et al ., ; Strand et al ., ). DNA from all samples was analyzed for DNA methylation using the 450K array by The Genome Centre Barts and the London School of Medicine and Dentistry, London, UK, as described previously (Strand et al ., ).…”
Section: Methodsmentioning
confidence: 98%
“…In considering richer sources of potential biomarkers for early prostate cancer, DNA hypermethylation is by far the most diverse and prevalent genomic aberration. It is found at higher levels in cancer tissues compared with benign histological samples such as normal/adjacent normal, benign prostate hyperplasia, and prostatic intraepithelial neoplasia . Its stability and ease of detection in archival tissues further enhance the feasibility and appeal of its use in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one epigenetic assay, ConfirmMDx, is commercially available, which measures methylation at APC , GSTP1 , and RASSF1 loci, and is intended for use on benign prostate biopsies to identify men who are likely to have cancer in a subsequent biopsy. This test, designed to detect molecular features of a field cancerization effect, represents a challenging application since field effects are reportedly variable in time and space . It is, therefore, not surprising that this test shows limited specificity (64%) and sensitivity (66%) with an overall misclassification rate exceeding 35% .…”
Section: Discussionmentioning
confidence: 99%